Allelopathic Effects of Sorghum Bicolor Aqueous Extracts on the Growth and Biochemicals Responses of Raphanus Sativus L. - Ali, Samrin; Khan, Wasim; Ali, Mansoor; Bibi, Sana; Bibi, Sania; Ejaz, Sania; Ali, Sana; Rasheed, Shayan; Safia Gul, Safia Gul; Khan, Muhammad Ishaq; Ahmad, Adnan Ali (Indus Journal of Bioscience Research, 2025)
This study investigates the allelopathic effects of aqueous extracts from Sorghum bicolor on the germination and growth of Raphanus sativus seedlings. Leaf and stem extracts were applied at control (0%), low (3%), medium (5%), and high (6%) concentrations, and their impacts were evaluated through parameters such as germination percentage, shoot and root length, fresh and dry weight, and number of leaves. Both extracts significantly inhibited germination and growth, with higher concentrations (5% and 6%) causing pronounced reductions in germination rates (down to 50%), root and shoot length, and biomass accumulation. Stem extracts exhibited a more consistent inhibitory effect, particularly on root and shoot dry weight, while leaf extracts showed variable effects, including slight stimulation of shoot fresh weight at lower concentrations. Additionally, higher extract concentrations increased chlorophyll, carotenoid, flavonoid, phenolic, and sugar content, as well as indole acetic acid (IAA) levels, suggesting stress-induced compensatory responses in Raphanus sativus. These findings confirm the allelopathic potential of Sorghum bicolor, particularly its phenolic compounds, and highlight the need for cautious application in agricultural weed management to minimize adverse effects on crop growth and yield.